Early Childhood Digital Literacy: Integrating Parental Guidance, Islamic Content, and Technology-Based Learning - Novia Maulana, Ade; Warmansyah, Jhoni; Wan Yaacob, Wan Mohd Yusoff (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Digital transformation has changed the learning patterns of preschool children globally; however, studies that integrate Islamic education perspectives on digital literacy for preschool children remain limited, especially in Indonesia. This research aims to analyze Muslim parents' involvement in digital-based learning activities and its influence on preschool children's digital literacy in Jambi from an Islamic education perspective. This qualitative research with a case study design involved fifteen Muslim families as primary informants and three early childhood educators as additional informants selected purposively. Data were collected through participatory observation, semi-structured in-depth interviews, and visual documentation over six months, then analyzed using the Miles and Huberman interactive model. The research found three main dimensions: patterns of parental involvement based on Islamic tarbiyah values through establishing device usage schedules based on worship times and integration of prayer rituals, dominance of Islamic-nuanced educational content such as Quranic learning applications and exemplary stories, and progressive development of children's digital literacy encompassing technical skills, content selection according to Islamic standards, understanding of moral messages, and multilingual cognitive enhancement. This research concludes that the traditional concept of Islamic tarbiyah can be adapted to the digital era through the principle of wasathiyah, which balances technology utilization with the preservation of aqidah and akhlaq, proving that technology can become a positive educational wasilah when guided by Islamic values. This research provides an Islamic digital parenting framework that can be adopted by Muslim parents, Islamic educational institutions, and policymakers in optimizing preschool children's digital literacy based on Islamic values.